Cash Flow and Net Working Capital as Determinants of Cash Holdings: A Case Study of Mining Companies Listed on the Indonesia Stock Exchange - Armelia, Rifka Resti; Razak, Linda Arisanty; Ramly, Ramly (Jurnal Akuntansi, 2025)
Purpose – The purpose of this research is to investigate how cash holdings in mining businesses listed on the Indonesia Stock Exchange (IDX) is influenced by cash flow and net working capital. Design/Methodology/Approach – A quantitative approach was adopted using explanatory research methods. The data consist of financial statements from mining sector companies covering the period 2020–2024. Hypothesis testing and data analysis were conducted using EViews 12 software. Findings – Research results show that cash flow and net working capital have a significant influence on cash holding. Therefore, an increase in both of these variables can increase the company's cash holding. Research limitations/Implications – Company management should place greater emphasis on managing cash flow and net working capital effectively toenhance financial stability and mitigate liquidity risks. The findings of this research are expected to serve as a valuable reference for financial decisionmaking among practitioners and academics within the mining industry. Keywords: Cash Flow, Cash Holding, Liquidity, Mining Companies, Net Working Capital